2014
DOI: 10.1016/j.pharep.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Il-1β, Il-2, Il-6, TNFα in the blood serum in children with generalized epilepsy treated by valproate

Abstract: The serum level of pro-inflammatory IL-6 in patients with generalized epilepsy decreased in statistically significant way during VPA therapy, so the anti-inflammatory properties of VPA are also important for the effective control of seizure. Due to the incompatibility of reports on the influence of VPA on cytokine system in patients with generalized epilepsy, this problem needs more investigations, especially in the group of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Partial seizures without impairment of consciousness with simple symptomatology and possessing an origin in neocortex is a subclass of focal epileptic seizures, whereas partial seizures with impairment of consciousness with complex symptomatology and originating in old cortical structures of the temporal lobe (or for some cases in orbitofrontal cortex) is another type (1,2). When considering generalised seizures, there is an onset recorded simultaneously in both cerebral hemispheres (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial seizures without impairment of consciousness with simple symptomatology and possessing an origin in neocortex is a subclass of focal epileptic seizures, whereas partial seizures with impairment of consciousness with complex symptomatology and originating in old cortical structures of the temporal lobe (or for some cases in orbitofrontal cortex) is another type (1,2). When considering generalised seizures, there is an onset recorded simultaneously in both cerebral hemispheres (3).…”
Section: Introductionmentioning
confidence: 99%
“…This complexity of genetical approach is directing researchers to analyse processes underlying epilepsy in area of biological-pathway-based approach. Besides, epilepsy is not defined as a single disorder but rather a group of syndromes with a variety of underlying diseases, and also neurotransmitter distributions or other metabolic problems are supposed to involve in epileptogenesis (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that as epilepsy treatment progressed, the levels of neuroinflammatory mediators decrease. 16,31,32 The reason for the obtained result in the present study was presumed to be the difference in the commonly used antiepileptic drugs between humans and dogs. In human-based epilepsy studies that reported a decrease in inflammatory mediators with the progression of epilepsy treatment, valproic acid was mainly administered.…”
Section: Correlation Of Serum Hmgb1 Concentration With the Durationmentioning
confidence: 59%
“…In human-based epilepsy studies that reported a decrease in inflammatory mediators with the progression of epilepsy treatment, valproic acid was mainly administered. 16,32 Anti-inflammatory effect of valproic acid has been reported; however, there are no reports of the anti-inflammatory effects of phenobarbital and KBr, which are commonly administered One recent study demonstrated that serum HMGB1 concentration increases immediately after a generalized convulsive seizure and remains elevated for 6 hours. 34 The times for each acquired serum sample after seizure varied in this study and thus, it is possible that variations in collection timing influenced the analysis of the correlation between seizure frequency and serum HMGB1 level.…”
Section: Correlation Of Serum Hmgb1 Concentration With the Durationmentioning
confidence: 99%
“…IL-6 is an early-stage inflammatory factor, and despite its protective effect on brain tissue, long-term overexposure will not only result in the augmentation of neuroglia, but also cause variations in tissue morphology, thus aggravating epilepsy ( 18 ). IL-2 can regulate the balance of lymphocytes, shorten epilepsy latency and decrease the threshold value for extending the onset of epileptic discharge ( 19 ). This study showed that serum HMGB-1 levels were positively correlated with the levels of IL-2 and IL-6.…”
Section: Discussionmentioning
confidence: 99%